Potential effect dietary supplementation of calcium tetraborate in quails exposed to cadmium: Its impact on productive performance, oxidative stress, cecal microflora, and histopathological changes - Mutlu, Muhsin; Simsek, Ulku Gulcihan; Iflazoglu, Sera; Yilmaz, Aysen; Karabulut, Burak; Incili, Canan Akdeniz; Mutlu, Seda Iflazoglu (Academic Press Inc Elsevier Science, 2024)
Cadmium (Cd) is a ubiquitous environmental pollutant, and Cd exposure harms human health, agriculture, and animal husbandry. The present study aimed to investigate the potential protective effect of dietary supplementation of calcium tetraborate (CTB) on productive performance, oxidative stress, cecal microflora, and histopathological changes in quail exposed to Cd. A total of one hundred twenty, 6-week-old Japanese quail (four females and two males/replicate) were divided into four groups (30 quails/group): the control group (feeding basic diet), CTB group (basic diet containing 300 mg/kg CaB4O7, 22.14% elemental B/kg diet), the Cd group (basic diet containing 100 mg/kg cadmium chloride (CdCl2) (total Cd content of 92.1 mg/kg)) and the CTB + Cd group (basic diet containing 300 mg/kg CTB and 100 mg/kg CdCl2). The results showed that Cd exposure caused decreased performance, increased the proportion of broken and soft-shelled eggs, induced oxidative stress, affected cecal microflora, epicardial hemorrhages in the heart, focal necrosis in the liver, degeneration in the kidneys, and degenerated and necrotic seminiferous tubules in the testicles. CTB prevented Cd-induced oxidative stress in liver tissue by increasing total antioxidant status and reducing total oxidant status. In addition, CTB improved egg production and feed conversion ratio (FCR). CTB protected the cecal microflora by inhibiting Enterobacteriaceae and promoting Lactobacillus. CTB also reduced Cd-induced histopathological damage in the heart, liver, kidneys, and testicles. In conclusion, these findings suggest that CTB could be used in Cd-challenged quail, and this compound provides new insights into the toxicity of environmental Cd.
Keywords: Calcium tetraborate; Cadmium exposure; Histopathology; Microflora; Oxidative stress; Quail